Government’s Strategy in Maintaining Economic Resilience during the Covid-19 Pandemic - Mujiyanto, Mujiyanto; Sahabuddin, Zaenal Abidin; Saputro, Guntur Eko (Yayasan Sembilan Pemuda Indonesia, 2023)
The threat of recession stalks the world’s economies, including Indonesia. It has also been warned by the world’s economists of the coming storm of global recession. This is evidenced by the slowdown in global economic growth, namely the United States, China and the European Union. This threat is a non-military threat, so it is necessary to determine a strategy to deal with it so that the Indonesian economy can survive. This paper aims to examine the Indonesian government’s strategy in anticipating the economic impact of Covid-19 through fiscal and monetary policies. This research uses literature study with a descriptive approach. The conclusion that can be drawn is that the government needs to continue to evaluate and adjust policies according to developing conditions.